Multi-touch human-computer interface B - Ong, Yee Yer. (2013)
With the increasingly popularity of multi-touch interfaces, devices that support multi-touch are getting a surge in sales and becoming increasingly common. As users experience is being enhanced by the interaction multi-touch devices provide, research communities are starting to explore the different alternatives towards creating multi-touch screens, as the existing methods available on portable devices are difficult to recreate for home projects. In this project, optical based solution for multi-touch interaction, Laser Light Plane (LLP) is being used.